Central African Economic and Monetary Community : Recent Developments and Regional Policy Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines recent developments and regional policy issues for the Central African Economic and Monetary Community (CEMAC). The CEMAC region benefited in 2000-01 from favorable world oil prices. This helped to improve the public finances and to strengthen the reserve position of the Central Bank of Central African States. But inflation increased to 4 percent in 2001, owing to pressures from high domestic demand growth, which rose by 12 percent in real terms, and was fed by growth in credit to governments. Prospects for 2002 are for continued strong growth in domestic demand.